TikTok/Flipgrid for Foreign Language Learning in Higher Education: A Case Study - Pérez Sabater, Carmen; Cerezo Herrero, Enrique; Barbasán Ortuño, Inmaculada (Íkala, Revista de Lenguaje y Cultura, 2023)
The interweaving of in-person and online teaching at the university level requires the implementation of new resources that allow the coexistence of these two forms of education. To that end, we addressed the incorporation of TikTok and FlipGrid at the university for speaking practice in the foreign language classroom. We compared the results of this teaching experience in three courses, in two foreign languages, English B2 and Italian A2, in engineering degrees. The methodological design of this research comprised a classroom intervention, an analysis through surveys, and feedback sessions. The results indicate that the use of short videos for speaking practice is motivating and enriching in all the study groups and in both languages, although the participants do not consider the use of TikTok appropriate at university. In FlipGrid, on the other hand, there have been no doubts about its suitability for academic purposes. Besides, the comparison between languages, and therefore levels, indicates that Italian A2 learners view TikTok with a more positive attitude than those of English B2. Our findings bring to the fore the potential of short video recording and the need to link the academic and social contexts for a more well-rounded educational experience.